Influence of Non-conventional Sperm Quality Parameters on Field Fertility in Ovine - Mendoza, Noelia; Casao, Adriana; Domingo, Juan; Quintín, Francisco; Laviña, Adolfo; Fantova, Enrique; Cebrián-Pérez, José Álvaro; Muiño-Blanco, Teresa; Pérez-Pe, Rosaura (Frontiers in Veterinary Science, 2021)
The prediction of the fertilizing ability of a seminal dose continues to be a primary aim in the field of artificial insemination (AI). To achieve this goal, in this study we have included the evaluation of some non-conventional sperm quality markers. A total of 3906 ewes from 52 different farms were inseminated with 357 refrigerated seminal doses obtained from 45 mature Rasa Aragonesa rams. The same samples were used for sperm quality analysis including membrane integrity, capacitation status, oxygen consumption and apoptotic-like markers such as phosphatidylserine translocation (PS), plasmalemma disorganization/mitochondrial membrane potential, caspase activation and DNA damage. Seminal doses from the breeding (B) season presented higher percentages of intact membrane (IM), non permeant (NP) membrane with high mitochondrial membrane potential (ΔΨm) and IM without PS translocation spermatozoa than those from the non-breeding (NB) season. Therefore, we can conclude that there were less spermatozoa showing apoptotic-like features in the seminal doses from the B than the NB season, although these differences did not affect field fertility. Only the percentage of intact membrane, non-capacitated (IM-NC) spermatozoa showed a significant correlation with in vivo fertility (P=0.005) and fecundity (P=0.007) values obtained after cervical AI when all data were evaluated. When the data were sorted by season and distance to the farms where AI was performed, the correlation between the percentage of IM-NC spermatozoa and reproductive parameters increased in the NB season and progressively with remoteness from the farms. Some other sperm parameters, like NP with high ΔΨm, IM sperm without active caspases and DNA-intact spermatozoa, also showed significant correlations with the reproductive parameters in the sorted data. Moreover, the increment in both the percentage of IM-NC and DNA-intact spermatozoa would increase the probability of obtaining a fertility higher than the mean (>52%), as revealed by a multiple logistic regression analysis. In conclusion, we have identified two seminal markers - the percentage of intact membrane, non-capacitated spermatozoa, and DNA intact spermatozoa - which could be used as a test to discard males in AI programs, which is highly important from an economic point of view and can contribute to achieving satisfactory fertility rates.